Extraction of Rhenium with Trialkylbenzylammonium Chloride - I. A. Kalina; E. V. Zlobina; Zh. Zh. Bekishev; A. G. Ismailova; Kh. S. Tassibekov; Z. A. Iskakov; B. Zh. Toksanbayev; A. T. Kumarbekova; A. S. Fomenko (Metals)
This study investigates the extraction of rhenium using trialkylbenzyl ammonium chloride (TABAC) as an alternative to trialkylamine (TAA) for recovering rhenium from highly diluted solutions. Rhenium, present as ReO4− over a wide acidity range, was extracted via an anion exchange mechanism in single-stage experiments monitored by inductively coupled plasma mass spectrometry (ICP-MS). Key variables, including pH, acid concentration, and the concentrations of extractant and metal, were examined. The results demonstrated a high extraction efficiency exceeding 99% within a pH range of 2 to 7 and from solutions containing sulfuric or hydrochloric acid at concentrations of 0.1 to 3.0 M (mol/L). However, extraction from nitric acid solutions was less efficient, with less than 30% recovery. Performance for both TAA-kerosene and TABAC-kerosene followed the order H2SO4 > HCl > HNO3. The optimal TABAC concentration was 10−2 M (mol/L) in kerosene. TABAC also showed higher selectivity than TAA, with separation coefficients Re/Mo = 66.8 and Re/W = 55.8 in 0.1–1.0 M (mol/L) sulfuric acid. Based on equilibrium studies, the complexes formed during extraction were identified as [R3R′NH]ReO4. This approach may offer environmentally friendly and cost-effective benefits for large-scale industrial applications, enabling efficient recovery of valuable rhenium while reducing waste and environmental impact.